1982
DOI: 10.1295/polymj.14.137
|View full text |Cite
|
Sign up to set email alerts
|

Homogeneous Polymerization of Methyl Methacrylate Initiated by Potassium Salts of Methanol and t-Butyl Alcohol in the Presence of Cryptand [222]

Abstract: ABSTRACT:Homogeneous polymerization of methyl methacrylate initiated by potassium salts of methanol and t-butyl alcohol was studied in toluene in the presence of cryptand [222). The polymers prepared were predominantly syndiotactic. The isotacticities increased slightly with an increase in temperature. More than thirty years ago, it was claimed that alkali metal salts of primary alcohols could not initiate the polymerization of methyl methacrylate (MMA) in ether.' More recently, the oligomerization of MMA by C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1984
1984
2008
2008

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…The value of the persistence ratio, ρ, is close to unity, indicating that the monomer addition follows Bernoullian statistics. These results are similar to those found with a cryptated potassium counterion in toluene …”
Section: Resultssupporting
confidence: 90%
“…The value of the persistence ratio, ρ, is close to unity, indicating that the monomer addition follows Bernoullian statistics. These results are similar to those found with a cryptated potassium counterion in toluene …”
Section: Resultssupporting
confidence: 90%
“…It has been shown that complexing agents of alkali metals increase the reactivity of active centers in anionic polymerization ,, and allow the initiation of heterocyclic monomers . In order to increase the propagation rate, polymerizations were performed in presence of 18-crown-6.…”
Section: Resultsmentioning
confidence: 99%
“…Additives that have been used in alkyl (meth)acrylate polymerization are alkali metal salts of alkoxide, [22] halides, [6] perchlorates, [23] alkyl silanolates, [24] aluminium alkyls, [25][26][27] and chelating additives such as crown ethers, [28] cryptands, [29,30] pyridine, [31] N,N,N 0 ,N 0 -tetramethylethylenediamine (TMEDA), [32,33] aminoalkoxides, [34] monoalkoxyalkoxides [35,36] and polydentate dilithiumalkoxides. [37] All of these additives coordinate with propagating enolate ion-pairs with different efficiencies and render certain degree of control to the polymerization.…”
Section: Introductionmentioning
confidence: 99%